Chalcogenide nanocomposite electrodes grown by chemical etching of Ni‐foam as electrocatalyst for efficient oxygen evolution reaction. (29th November 2019) - Deokate, Ramesh J.; Mujawar, Sarfraj H.; Chavan, Harish S.; Mali, Sawanta S.; Hong, Chang Kook; Im, Hyunsik; Inamdar, Akbar I.
Summary: We report on the synthesis of NiSSe nanocomposite by chemical etching of Ni‐foam using simple solvothermal technique and investigated it as an electrocatalyst for the oxygen evolution reaction (OER). Different morphologies such as nanograins, branched mesh‐like architecture, and agglomerated nanograins with nanoporous are obtained for NiSSe, NiSe, and NiS, respectively. The overpotentials of 247, 266, and 329 mV (vs RHE) are obtained to attain a current density of 30 mA cm −2 for NiSSe, NiS, and NiSe nanocomposites, respectively. Interestingly, ternary nanocomposite reaches a high current density of 100 mA cm −2 by operating only at an overpotential of 342 mV. The low Tafel slope of 175.7 mV dec −1 reveals that the ternary nanocomposite consists of most favorable catalytic kinetics for mass and electron transport during the OER reaction. The improved catalytic performance of NiSSe nanocomposite is attributed to the synergy between electrochemcial surface area and improved electronic conductivity. Abstract : In this work, we directly fabricated chalcogenide NiSSe nanocomposite onto the Ni‐foam substrate via simple one‐step hydrothermal technique, which can be used as highly efficient catalyst for the oxygen evolution reaction (OER). It showed a low overpotentials of 247 mV (vs RHE) to attain a current density of 30 mA cm −2, and the lower Tafel slope of 175.7 m Vdec −1 reveals that the ternary nanocomposite consists of most favorable catalytic kinetics for mass and electron transport during the OER reaction.